2007
DOI: 10.1529/biophysj.106.097345
|View full text |Cite
|
Sign up to set email alerts
|

Ergosterol in POPC Membranes: Physical Properties and Comparison with Structurally Similar Sterols

Abstract: The physical properties of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC)/ergosterol bilayers in the liquid-crystalline phase were determined using deuterium nuclear magnetic resonance ((2)H NMR) and vesicle extrusion. For the (2)H NMR experiments, the sn-1 chain of POPC was perdeuterated, and spectra were taken as a function of ergosterol concentration and temperature. Analysis of the liquid-crystalline spectra provides clear evidence that two types of liquid-crystalline domains, neither of which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
61
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 39 publications
17
61
3
Order By: Relevance
“…The remaining 120 ns were analyzed with AmberTools14 [48] and GROMACS version 4.6.5[64,65], taking snapshots every 20 ps to yield 6000 snapshots in total per system.As discussed in detail later, the simulations performed in this study indicate that Erg orders POPC bilayers more than Chol at 30 mol-%.This observation is in conflict with literature since at 30 mol-%, Chol orders a membrane of monounsaturated lipids such as POPC more efficiently[66][67][68]. The effects of Erg on the bilayer are believed to saturate at around 25 mol-% Erg[66][67][68]. On the contrary, Erg has a greater ordering effect than Chol on saturated membranes due to the rigidity of its tail, which results in smaller tilt angles of the sterol ring sysTo resolve if this discrepancy was a force field related issue, we reran the simulations of Chol in POPC and Erg in POPC employing the CHARMM force field C36c[70].…”
contrasting
confidence: 85%
See 1 more Smart Citation
“…The remaining 120 ns were analyzed with AmberTools14 [48] and GROMACS version 4.6.5[64,65], taking snapshots every 20 ps to yield 6000 snapshots in total per system.As discussed in detail later, the simulations performed in this study indicate that Erg orders POPC bilayers more than Chol at 30 mol-%.This observation is in conflict with literature since at 30 mol-%, Chol orders a membrane of monounsaturated lipids such as POPC more efficiently[66][67][68]. The effects of Erg on the bilayer are believed to saturate at around 25 mol-% Erg[66][67][68]. On the contrary, Erg has a greater ordering effect than Chol on saturated membranes due to the rigidity of its tail, which results in smaller tilt angles of the sterol ring sysTo resolve if this discrepancy was a force field related issue, we reran the simulations of Chol in POPC and Erg in POPC employing the CHARMM force field C36c[70].…”
contrasting
confidence: 85%
“…The remaining 120 ns were analyzed with AmberTools14 [48] and GROMACS version 4.6.5[64,65], taking snapshots every 20 ps to yield 6000 snapshots in total per system.As discussed in detail later, the simulations performed in this study indicate that Erg orders POPC bilayers more than Chol at 30 mol-%.This observation is in conflict with literature since at 30 mol-%, Chol orders a membrane of monounsaturated lipids such as POPC more efficiently[66][67][68]. The effects of Erg on the bilayer are believed to saturate at around 25 mol-% Erg[66][67][68].…”
mentioning
confidence: 61%
“…4B). Importantly, extensive solid-state NMR studies have demonstrated that the incorporation of either ergosterol or lanosterol into POPC liposomes causes very similar changes in global membrane properties (61)(62)(63). In the event, titrating AmB with sterol-free and then 10% ergosterol-containing POPC LUVs again caused a substantial increase in the observed net exotherm.…”
Section: Resultsmentioning
confidence: 99%
“…Possible reasons why indirect determinations of phase boundaries by fluorescent probes could be misleading are discussed in reference (6), although the appropriate conditions were fulfilled in reference (25). Interestingly, fluid-fluid phase separation is observed as two-component 2 H-NMR spectra in binary mixtures of POPC with ergosterol, although this is said not to involve a L o -phase (43) and such twocomponent spectra are not observed with POPC/chol mixtures (9).…”
Section: Discussionmentioning
confidence: 99%